The CACNA1C risk allele selectively impacts on executive function in bipolar type I disorder. (14th February 2013) - Soeiro‐de‐Souza, M. G.; Bio, D. S.; Dias, V. V.; Vieta, E.; Machado‐Vieira, R.; Moreno, R. A.
<x xml:space="preserve">Abstract</x> Objective Calcium channels are important for converting electrical activity into biochemical events. A single nucleotide polymorphism (SNP) (rs1006737) in the CACNA1C gene has been strongly associated with increased risk for Bipolar disorder (BD) in genome‐wide association studies. Recently, this same SNP has been reported to influence executive function in schizophrenia and controls, but it remains unclear whether this SNP affects behaviour, especially cognition in subjects with BD. Method A total of 109 BD type I subjects and 96 controls were genotyped for CACNA1C rs1006737 and assessed with an executive function tests battery [Wechsler Adult Intelligence Scale III (WAIS‐III) Letter‐Number Sequence subtest (WAIS‐LNS), digit span (WAISDS), trail making test (TMT), and WCST (Wisconsin Card Sorting Test)]. Results In patients with BD, the CACNA1C genotype Met/Met was associated with worse performance on all four executive function tests compared to Val/Val. No influence of CACNA1C was observed in the cognitive performance of healthy controls. Conclusion Our data indicate for the first time that the CACNA1C risk allele is likely associated with executive dysfunction as a trait in BD, as this association was found regardless the presence of mood symptoms. Larger studies should evaluate the potential influence of CACNA1C on other cognitive domains in BD.